2019
DOI: 10.1029/2019gl084529
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling at‐a‐Station and at‐Many‐Stations Hydraulic Geometry Through River‐Wide Geomorphology

Abstract: At‐many‐stations hydraulic geometry (AMHG), while useful for estimating river discharge from satellite data, remains empirical and has yet to be reconciled with the at‐a‐station hydraulic geometry (AHG) from which it was originally derived. Here we present evidence, using United States Geological Survey field measurements of channel hydraulics for 155 rivers, that AMHG can be hydraulically and geomorphically reconciled with AHG. Our results indicate that AMHG is rightly understood as an expression of a river‐w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…Furthermore, the at‐many‐stations hydraulic geometry (AMHG) which is an extension to the classic AHG theory showed that the empirical parameters of AHG (valid at cross‐sections) are functionally related along a river (Gleason & Wang, 2015). The incorporation of AMHG could lead to further constraining the prior and posterior distributions of river discharge, as it is reconcilable with AHG (Brinkerhoff et al, 2019), making AMHG a promising approach for an algorithm such as SAD. Alternatively, other discharge estimation approaches that only depend on hydraulic geometry relations (e.g., Dingman & Sharma, 1997; López et al, 2007) Finally, the implementation of the SAD algorithm presented here is not applicable to an entire river network because it does not take into account any flows at junctions or from lateral tributaries.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the at‐many‐stations hydraulic geometry (AMHG) which is an extension to the classic AHG theory showed that the empirical parameters of AHG (valid at cross‐sections) are functionally related along a river (Gleason & Wang, 2015). The incorporation of AMHG could lead to further constraining the prior and posterior distributions of river discharge, as it is reconcilable with AHG (Brinkerhoff et al, 2019), making AMHG a promising approach for an algorithm such as SAD. Alternatively, other discharge estimation approaches that only depend on hydraulic geometry relations (e.g., Dingman & Sharma, 1997; López et al, 2007) Finally, the implementation of the SAD algorithm presented here is not applicable to an entire river network because it does not take into account any flows at junctions or from lateral tributaries.…”
Section: Discussionmentioning
confidence: 99%
“…1. Update BAM to reflect the latest geomorphic understanding of AMHG following Brinkerhoff et al (2019) and ingest geomorphic priors (section 3.1).…”
Section: Methodsmentioning
confidence: 99%
“…Our first task was to gather a comprehensive data set of measured river hydraulics to generate training data. We started with Brinkerhoff et al's (2019) data set. This data set merges USGS surface water measurements (NWIS; https://waterdata.usgs.gov/nwis/measurements) of channel discharge and geometry with the NHD (https://www.epa.gov/waterdata/nhdplus-national-hydrography-dataset-plus) and filters the data to include only those rivers that have at least six stations of 20 measurements each to derive that river's AMHG.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…that drainage area threshold. This procedure follows general hydraulic correlations between channel size, slope, total discharge, and n (Brinkerhoff et al, 2019). Hillslope flow is modelled as an explicit kinematic wave for non-channelized flow (Li et al 1975), which requires a surface roughness coefficient (i.e., hillslope friction), and we limit hillslope friction to between 0.05 (non-dimensional; a hillslope with friction equivalent to a rough channel) and 25 (a hillslope with extreme friction to approximate slow interflow through weathering crust).…”
Section: Model Calibrationmentioning
confidence: 99%